Pandangan Kekristenan Mengenai Praktik Spiritisme Berlandaskan Alkitab - Zega, Desriaman; Mangoli, Yefta Yan (Jurnal Ap-Kain, 2024)
Spiritualism is a person's view or belief that people who have died that people who have died still have a relationship with people who are still alive. The relationship referred to in this case is that people who have died can be communicated or dialogued with. can be invited to communicate or dialogue. Well, this is often done by Christians who believe in the Lord Jesus. Therefore, through this article, the author tries to find answers regarding the biblical view of spiritualism. towards the practice of spiritualism. This research uses a qualitative method with a descriptive approach with sources from the Bible and literature related to the topic. literature related to the topic of discussion. Based on the results of the research conducted through the study of the Bible and literature related to the topic, it can be explained that people who have died have no relationship with the living and the practice of spiritism is a behavior that is against the Christian faith. contrary to the Christian faith. God is strongly against the practices of spiritism in any form. In fact, anyone who practices spiritism will not inherit the kingdom of heaven.AbstrakSpiritualisme adalah pandangan atau keyakinan seseorang bahwa orang-orang yang telah meninggal masih memiliki hubungan dengan orang-orang yang masih hidup. Hubungan yang dimaksud dalam hal ini adalah bahwa orang-orang yang telah meninggal dapat diajak berkomunikasi atau berdialog. Nah, ini sering dilakukan oleh umat Kristiani yang percaya kepada Tuhan Yesus. Oleh karena itu, melalui artikel ini, penulis mencoba mencari jawaban mengenai pandangan Alkitab terhadap praktik spiritisme. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif dengan sumber dari Alkitab dan literatur yang terkait dengan topik pembahasan. Berdasarkan hasil penelitian yang dilakukan melalui studi Alkitab dan literatur yang terkait dengan topik pembahasan, dapat dijelaskan bahwa orang-orang yang telah meninggal tidak memiliki hubungan dengan orang-orang yang masih hidup dan praktik spiritisme adalah perilaku yang bertentangan dengan iman Kristiani. Tuhan sangat menentang praktik-praktik spiritisme dalam bentuk apapun. Bahkan, siapa pun yang mempraktikkan spiritisme tidak akan mewarisi kerajaan surga.